Lymphatic Improvement after Suction-assisted Lipectomy in a Lipedema Patient - Carolina de Souza Ribeiro Vitorasso, MD; Anna Carolina Borges Silva, MD; Bernardo Pinheiro de Senna Nogueira Batista, MD, PhD; Fábio Kamamoto, MD, MSc, PhD (Plastic and Reconstructive Surgery, Global Open, 2023)
Summary:. Lipedema is a chronic and progressive disease that may compromise lymphatic function. Although suction-assisted lipectomy (SAL) is considered a safe treatment for lipedema patients, the lymphatic repercussions of this surgical procedure are not fully understood. There is not enough evidence to support the role of SAL in lymphatic function treatment in lipedema. Here, we report a case of lymphatic drainage improvement after lipedema treatment with SAL. Tumescent SAL was performed in the deep subcutaneous layer, preserving the superficial and muscular lymphatic vessels. Pre- and postsurgical lymphoscintigraphy was equally documented under the Genoa protocol. A 34-year-old female patient presented with painful enlargement of the arms and lower limbs caused by lipedema. The patient had undergone conservative treatment with mild improvement in pain and heaviness. Lymphoscintigraphy showed slowed radiotracer progression on the left lower limb, collateral and tortuous lymphatic vessels on the right lower limb, and exuberant radiopharmaceutical concentration on the inguinal chain. Nine months after SAL was performed, the patient underwent another lymphoscintigraphy, which exhibited normalized radiopharmaceutical progression time and normal and symmetrical lymphatic vessel patterns. Collateral lymphatic paths and tortuosity vessels were no longer identified. Furthermore, the patient reported significant improvement in pain and the limb’s appearance. Tumescent SAL is not only efficient and safe in treating lipedema, but may also be responsible for improvement in lymphatic drainage in lipedema patients. Additional prospective studies are fundamental to reinforce the current evidence and possibly yield predicting information about the tumescent liposuction eligibility in the improvement of lymphatic drainage.